2010
DOI: 10.1111/j.1551-2916.2010.04136.x
|View full text |Cite
|
Sign up to set email alerts
|

Thin‐Film Thermocouples Based on the System In2O3–SnO2

Abstract: Ceramic thermocouples are being developed to replace noblemetal thermocouples that are unable to withstand the harsh environments inside the hot sections of turbine engines used for power generation and propulsion. A number of alloys in the system indium oxide (In 2 O 3 ):tin oxide (SnO 2 ) were systematically investigated as thermocouples. Specifically, solid solutions containing up to 10 wt% SnO 2 were initially tested relative to a platinum reference electrode and the resulting thermoelectric properties wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…The SnO x can possibly fulfil some of these demands and because of that their TE properties have to be exploited. Several reports have been published where SnO x is used as dopant in InO x alloys 3,4 , as alloy element in SnO 2 :Al doped with S 5 or SnO 2 doped with cobalt 6 and thermoelectric hydrocarbon gas sensor 7 . Spray pyrolysis 6 , laser pulse evaporation and magnetron sputtering 1,2 are some of the most used methods for the production of SnO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The SnO x can possibly fulfil some of these demands and because of that their TE properties have to be exploited. Several reports have been published where SnO x is used as dopant in InO x alloys 3,4 , as alloy element in SnO 2 :Al doped with S 5 or SnO 2 doped with cobalt 6 and thermoelectric hydrocarbon gas sensor 7 . Spray pyrolysis 6 , laser pulse evaporation and magnetron sputtering 1,2 are some of the most used methods for the production of SnO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of conductive oxide films gave significant differences from our findings. Chen [23] found In 2 O 3 resistivity of 22 mΩ·cm and maximum thermopower of −224 μV·K − 1 , and Gregory [24] found a maximum thermopower of +256 μV·K − 1 for ZnO. Though our resistivity measurements were 100 times greater than Chen, the fitted thermopower measurements were about twice the values of Chen and Gregory.…”
Section: Resultsmentioning
confidence: 43%
“…(9) in materials with electrons restricted to either the valence or conduction bands, modifications are invoked in the work function and bulk resistivity due to deviations in film density or grain size from bulk. For example, phonon drag of the electron flow has also been cited as contributing to variations of resistivity and thermopower for various films [23], with the thermopower due to the phonon drag (S g ) added to the thermopower due to electron drift (S D ).…”
Section: Resultsmentioning
confidence: 99%
“…All these factors make it the most promising candidate for TFTC at high temperature. Different approaches have been taken to improve the stability and thermoelectric performance of ITO thin film for the application in high-temperature strain sensors, thermocouples and thermoelectric devices [8][9][10], and it has been reported that the introduction of nitrogen could increase the thermoelectric property of ITO thin films at high temperature range [7]. However, the influence of the dopant concentration of nitrogen on the stability and thermoelectric properties of ITO films has not been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%